Hubungan Asupan Energi dan Aktivitas Fisik dengan Status Gizi Siswa-Siswi SMP Muhammadiyah 1 Surakarta. - Putri, Conivera Catur Bramerya Giyatno, Muwakhidah, SKM., M.Kes, Wahyuni, SKM, M.Kes (2017)
Introduction: The health status of adolescents should be increased to produce the next generation of healthy and productive in order to become a valuable national asset for sustainable development in the future. Over nutrition appears in adolescence tend to continue into adulthood and then can be a risk factor for degenerative diseases. Over nutrition happens because of an imbalance between intake and energy expenditure. Purpose: To determine the association of energy intake and physical activity to nutritional status of students in SMP Muhammadiyah 1 Surakarta. Research method: The research was an observational with cross sectional approach. The population was students grade VIII at SMP Muhammadiyah 1 Surakarta 52 students were selected through systematic random sampling method. The energy intake data was collected using food recall 24 hours method for 3 unconsecutive days and physical activity were obtained recall 24 hours physical activity method for 7 days. The data was analyzed using Pearson Product Moment test and Rank Spearman test. Result: Research shows that 90,4% of the subjects had low energy intake, 94,2% of the subjects had a light of physical activity levels, 67,3% of subjects had normal nutritional status. Conclusion: There was no association of energy intake to nutritional status of students in SMP Muhammadiyah 1 Surakarta (p= 0,050). There was no correlation between physical activity to nutritional status of students in SMP Muhammadiyah 1 Surakarta (p= 0,285). Keywords: energy intake, physical activity, nutritional status, students junior high school